2020
DOI: 10.3390/molecules25235533
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the NLRP3 Inflammasome

Abstract: Inflammasomes are protein complexes which are important in several inflammatory diseases. Inflammasomes form part of the innate immune system that triggers the activation of inflammatory cytokines interleukin (IL)-1β and IL-18. The inflammasome most studied in sterile inflammation and non-communicable disease is the NLRP3 inflammasome. Upon activation by diverse pathogen or disease associated signals, NLRP3 nucleates the oligomerization of an adaptor protein ASC forming a platform (the inflammasome) for the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 46 publications
1
70
0
1
Order By: Relevance
“…The NLRP3 inflammasome significantly contributes to neuroinflammation and age-related cognitive decline and is potently activated by Aβ [ 381 ]. Novel specific inhibitors of the NLRP3 inflammasome are currently in pre-clinical or clinical trials [ 382 ] (ifmthera.com/pipeline). MCC950 (also known as CP-456,773 and CRID-3), a potent inhibitor of NLRP3, promotes microglial clearance of Aβ, reduces Aβ accumulation, and improves cognitive function in APP/PS1 mice [ 383 , 384 , 385 , 386 ].…”
Section: Possible Intervention For Neuroinflammation In Admentioning
confidence: 99%
“…The NLRP3 inflammasome significantly contributes to neuroinflammation and age-related cognitive decline and is potently activated by Aβ [ 381 ]. Novel specific inhibitors of the NLRP3 inflammasome are currently in pre-clinical or clinical trials [ 382 ] (ifmthera.com/pipeline). MCC950 (also known as CP-456,773 and CRID-3), a potent inhibitor of NLRP3, promotes microglial clearance of Aβ, reduces Aβ accumulation, and improves cognitive function in APP/PS1 mice [ 383 , 384 , 385 , 386 ].…”
Section: Possible Intervention For Neuroinflammation In Admentioning
confidence: 99%
“…The NLRP3 inflammasome consists of the protein NLRP3 complexed with the proteins ASC and caspase-1, along with several accessory proteins, including NEK7 [ 39 ]. Formation of NLRP3 inflammasomes typically requires a priming step, in which the activated transcription factor Nuclear factor kappa beta (NF-kappaB) drives increased expression of NLRP3 and of pro-interleukin-1β and -18.…”
Section: Mechanisms Involved In the Priming And Activation Of Inflmentioning
confidence: 99%
“…In these models, TET2 -deficient macrophages showed upregulation of several inflammatory cytokines part of the NLRP3 inflammasome complex, which is known to contribute to both atherogenesis and MDS pathogenesis [ 67 ]. In particular, it has been shown that interleukin-1β upregulates the expression of P-selectin in endothelial cells, a known chemo-attracting agent for monocytes, currently evaluated as a possible actionable target in the setting of CHIP and MDS to decrease cardiovascular risk [ 68 , 69 ]. Another approach currently in evaluation is the use of vitamin C, taking into account the recent data on its role in restoring some TET2 functions [ 70 , 71 ].…”
Section: Clinical Implications Of Chip: a Focus On Cardiovascular mentioning
confidence: 99%